Nanoemulsion-Based Strategy for Maximizing Nitrofurantoin Absorption: In-vitro and In-vivo Investigations - Nanda, Gouri P.; Patel, Mrunali; Patel, Rashmin (Recent Advances in Drug Delivery and Formulation, 2023)
Background: The main objective of the current research work is to improve the absorption of Nitrofurantoin (NFT) by minimizing gastrointestinal (GI) intolerance and variations in its absorption by formulating the drug into a nanoemulsion (NE). Method: Based on the highest saturation solubility of NFT, soybean oil, transcutol HP, and labrafil M1944CS were selected as oil, co-surfactant, and surfactant, and a Smix ratio of 1:2 was selected based on pseudoternary phase diagrams. The formulation prepared with an equal ratio of oil and Smix exhibited the lowest globule size, highest zeta potential, and higher drug release and hence was selected for further evaluation. Result: Optimized formulation (NF5) showed improved membrane permeability against pure drug suspension (2.30 times) and marketed suspension formulation (1.43 times). NF5 exhibited similar % cell viability and % cell toxicity in Caco-2 cell lines compared to the marketed suspension. The relative bioavailability of NFT-NE was enhanced by 1.10 and 1.17 times compared to the marketed and pure drug suspension, respectively. Conclusion: Thus, it can be concluded that the optimized nanoemulsion formulation of NFT exhibited improved membrane permeability, comparable cell viability, and increased relative bioavailability. These findings suggest the potential of the nanoemulsion approach as a strategy to overcome the variability of oral absorption and GI intolerance of NFT.
Keywords: nanoemulsion